Kants' Groundwork of the metaphysics of morals : a commentary - Timmermann, Jens (Cambridge University Press, 2007)
The Groundwork of the Metaphysics of Morals is Kant's central contribution to moral philosophy, and has inspired controversy ever since it was first published in 1785. Kant champions the insights of 'common human understanding' against what he sees as the dangerous perversions of ethical theory. Morality is revealed to be a matter of human autonomy: Kant locates the source of the 'categorical imperative' within each and every human will. However, he also portrays everyday morality in a way that many readers find difficult to accept. The Groundwork is a short book, but its argument is dense, intricate and at times treacherous. This commentary explains Kant's arguments paragraph by paragraph, and also contains an introduction, a synopsis of the argument, six short interpretative essays on key topics of the Groundwork, and a glossary of key terms. It will be an indispensable tool for anyone wishing to study the Groundwork in detail.